Penguatan Peran Aparatur Desa Dalam Perencanaan Strategis Untuk Pembangunan Desa Berkelanjutan di Desa Kurungkambing - Purwanto, Agus Joko; Nasution, Vivi Indra Amelia; Hakim, Nong Ayu Triyanti Utami; Budiman, Rahmat; Akadira, Tora; Rachman, Ace Sriati; Wiradharma, Gunawan (STMIK Royal, 2025)
Kurungkambing Village, located in Mandalawangi District, Banten, has significant local potential that remains underutilized due to the lack of structured data and limited village planning capacity. The gap between local resource mapping and strategic planning poses a major challenge in achieving sustainable development. To address this issue, the Community Service Program (PkM) of Universitas Terbuka was designed to strengthen the capacity of village officials through training and mentoring in village potential mapping based on village planning worksheets. This approach follows four key stages: input, process, output, and impact, aimed at establishing a more systematic, data-driven, and sustainable village development plan. The PkM activities include field surveys, socialization, technical training, mentoring, and monitoring and evaluation. The primary objective of this program is to develop a village potential database as a foundation for formulating more accurate policies and development strategies. Village officials can create more effective and strategic data-driven policies with this database. The program's sustainability requires synergy between academics, local government, and the village community to ensure data-driven development that enhances community welfare.Keywords: database, planning capacity, strategic planning, sustainable development, village potential. Abstrak: Desa Kurungkambing, Kecamatan Mandalawangi, Banten, memiliki potensi lokal yang belum optimal karena keterbatasan data terstruktur dan kapasitas perencanaan desa. Untuk mengatasi permasalahan ini, Program Pengabdian kepada Masyarakat (PkM) Universitas Terbuka dirancang untuk memperkuat kapasitas aparatur desa melalui pelatihan dan pendampingan dalam pemetaan potensi desa berbasis lembar perencanaan desa. Pendekatan ini mengacu pada empat alur utama: masukan, proses, hasil, dan dampak, yang bertujuan untuk mewujudkan perencanaan pembangunan desa yang lebih sistematis, berbasis data, dan berkelanjutan. Kegiatan PkM ini melibatkan serangkaian tahapan, termasuk survei lapangan, sosialisasi, pelatihan teknis, pendampingan, serta monitoring dan evaluasi. Tujuan utama program ini adalah mengembangkan database potensi desa sebagai dasar dalam penyusunan kebijakan dan strategi pembangunan yang lebih akurat. Dengan adanya database ini, aparatur desa dapat merumuskan kebijakan berbasis data yang lebih efektif dan strategis. Keberlanjutan program membutuhkan sinergi antara akademisi, pemerintah daerah, dan masyarakat desa guna memastikan pembangunan berbasis data yang berorientasi pada kesejahteraan masyarakat.Kata kunci: database, kapasitas perencanaan, perencanaan strategis, pembangunan berkelanjutan, dan potensi desa.